ChemInform Abstract: Tandem Cyclization of a Bispyridinium Chloride: Facile Synthesis of Substituted Indolizines. Issue 11 (18th March 2014) - Costa, Marta; Noro, Jennifer; Brito, Alexandra; Proenca, Fernanda
Abstract The obtained title compounds can be easily further functionalized, e.g. via formylation or bromination.